D4N2024 Presentation Showcase – Thematic Session 3b: Examining linkages between climate change and food systems - Nihal, Saif; Salman, Verda; Bakshi, Bhawani; Makhijani, Drishti; Shrestha, Aroja M.; Ali, Hazrat; Khondker, Murshed-e-Jahan; Shakya, Prakriti; Sharma, Anjali; Babu, Swati Sinha (International Food Policy Research Institute, 2024)
D4N2024 Presentation Showcase – Thematic Session 3b: Examining linkages between climate change and food systems